Integrasi Nilai-Nilai Islam Dalam Kurikulum Berbasis STEM Di Sekolah Islam Terpadu - Iqbal Anas; Iswantir M (Program Studi Manajemen Pendidikan Islam, 2024)
This research aims to integrate Islamic values in the STEM-based curriculum (Science, Technology, Engineering, Mathematics) in order to form holistic student characters and competencies. This research was conducted using qualitative and quantitative approaches. The methodology used includes literature study, in-depth interviews with educators and curriculum experts, as well as surveys to students and teachers in several integrated Islamic schools. The results showed that the integration of Islamic values in the STEM curriculum can improve students' understanding not only in academic aspects but also in terms of morals and ethics. In particular, values such as honesty, cooperation, responsibility and discipline can be instilled through teaching that combines scientific concepts with Islamic teachings. In addition, this approach also encourages the development of critical thinking, creative and problem-solving skills that are indispensable in facing the challenges of the 21st century. Implementing a STEM-based curriculum integrated with Islamic values requires support from various stakeholders, including teachers, school administrators and education policy makers. The findings indicate the need for training and professional development for teachers to adopt this approach effectively. Overall, this study concludes that the integration of Islamic values in the STEM-based curriculum not only enables more meaningful and relevant teaching but also helps in shaping a generation with high character and competence, ready to contribute positively in society.